Capture dynamic of Premnotrypes uorax (Coleoptera: Curculionidae) and the Guatemalan pota to tuber moth Tocia solaniuora (Lepidoptera: Gelechiidae) in traps with different types of attractants in a pota to crop (Solanum phureja) - GALINDO-P., JULIO RICARDO; ESPAÑOLA, JEANNETIE AMPARO (Revista Colombiana de Entomología, 2004)
In the Experimental Center of Corpoica Tibaltatá. a crop of Solanum phureja was followed during the  entire developmental cycle to evaluate capture dynamics of the  potato weevil and  the Guatemalan potato tuber moth, considering two periods: befor e and after hilling. The traps used were selected from previous work that showed high capture and usefulness for evaluating behavior of the insect of interest.  For the potato weevil, net pitfall traps that contained parts of the potato plant as attractant, and traps  that contained the same insect in group of males and females as attractants, were used. Traps recommended by the Centro Internacional de la Papa (CIP) were used as controls. Each kind of trap reflected insect activity in different ways and together showed two stages of the crop in which adult potato weevils had a greater activity, which were emergence and nowering of the crop. In the case of the Guatemalan potato tuber moth, white sticky traps and traps that contained females of the same insect as an attractant, were used. Adult capture data were also taken from  the pheromone traps.  The different traps showed two different crop stages in which adult Guatemalan potato tuber moths showed greatest activity, which were tuber initialization and physiological maturity of the crop.